Oral cavity lesions in COVID-19 patient- a neglected and morbid clinical entity in current pandemic - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2021)
The novel coronavirus disease 2019 (COVID-19) is highly contagious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). COVID-19 infections are usually associated with acute respiratory symptoms along with fever, myalgia, fatigue, altered taste and smell sensation. However, some oral cavity manifestations have been found in COVID-19 patients. There is debate whether these oral cavity manifestations are due to SARS-CoV-2 infection or secondary to patient’s systemic condition. Currently research shows that SARS-CoV-2 affect the respiratory tract and other organs those have angiotensin converting enzyme 2 (ACE2) receptors. ACE2 receptors are abundantly present in the oral cavity tissues which prone for SARS-CoV-2 infection. The oral cavity lesions in COVID-19 patient ranges from ulcers in the oral cavity to candidiasis, recurrent herpes simplex, geographical tongue, mucositis and petechiae. COVID-19 infection significantly affects the oral cavity and salivary glands. Gustatory dysfunction or dysgeusia is a common oral cavity manifestation of COVID-19 patient. Clinicians should keep in mind about different lesions of the oral cavity and taste disturbances of the COVID-19 patients which will help the early diagnosis, treatment and avoid morbidity of the patient. There is still debate on exact cause for oral manifestations of the COVID-19 infections and its impact. This review article discusses the details of this neglected clinical entity such as oral cavity lesions in COVID-19 patients.